Transcription of Mangwilo xylophone music from film strips - Kubik, Gerhard (International Library of African Music, 1965)
The purpose of this paper is twofold: firstly to explain a method of transcribing African instrumental music, and secondly to give information on the structure of the Mangwilo xylophone music of the Alomwe and Ashirima in Northern Mozambique.
Keywords: Ethnomusicology; Xylophone music; Xylophone; Musical instruments; Mozambique; African Music; Xylophone (Instrument)